Pemahaman Mahasiswa tentang Etika Akademik: Pendekatan Studi Kasus Pada Akademi Keuangan Perbankan (AKUBANK) Nusantara - Putri Khairani (Jurnal Pendidikan Penggerak, 2023)
This research aims to gain a comprehensive understanding of the level of students' understanding of academic ethics at the Nusantara Banking Finance Academy (AKUBANK). This study uses a case study approach to explore the factors that influence the understanding of academic ethics, as well as their implications for the academic culture at this institution. The research method used is a case study involving AKUBANK Nusantara students as research subjects. Data was collected through in-depth interviews, questionnaires and observations. Data analysis was carried out using qualitative and quantitative approaches to comprehensively describe students' understanding of academic ethics. The research results show that AKUBANK Nusantara students already understand academic ethics. These findings provide valuable insights for higher education institutions in designing strategies to improve students' understanding of academic ethics. This study also contributes to the academic ethics literature by presenting the results of empirical research in the financial and banking education environment. Practical implications of this research include recommendations for developing academic ethics programs, increasing student awareness, and improving institutional policies to encourage a better academic culture.